HARGA DAN KUALITAS PRODUK TERHADAP KEPUTUSAN PEMBELIAN SERTA IMPLIKASINYA PADA KEPUASAN PELANGGAN (Studi Kasus Pada Merek ZARA Cabang Mall Kotakasablanka) - Yolanda; Cicih Ratnasih; Inggi Ratna Rangkuti (Fakultas Ekonomi Universitas Borobudur, 2022)
Abstract This study aims to determine the effect of price and product quality on purchasing decisions and their implications for customer satisfaction of the Zara Brand, Kota Kasablanka Mall Branch. The data used in this research is in the form of primary data collected from respondents' answers based on the questionnaire given, namely as many as 100 people. The data processing method uses the path analysis method (Path Analysis) with the help of SPSS version 23.0. Statistical testing using individual parameter significance test (t test) and simultaneous significance test (F test). The results showed that simultaneously the variables Price, Product Quality and Purchase Decision have a significant effect on Customer Satisfaction. Partially shows that the analysis: (1) the price variable has a significant effect on customer satisfaction, while the analysis (2) the product quality variable has a significant effect on customer satisfaction and on analysis, (3) the purchasing decision variable has a significant effect on customer satisfaction. Keywords: Price, Product Quality, Purchase Decision, Customer Satisfaction.